Taxane-derived compounds protect SK-N-SH cells against oxidative stress injury induced by H2O2. (3rd July 2017) - Duan, Ruisheng; Xing, Xing; Qi, Yachao; Yin, Nan; Hao, Hongyu; Chu, Hongshan; Gao, Ya; Wang, Weiping; Lv, Peiyuan
Abstract: Objective : Discussed the protection of taxane-derived compounds, 7-deacetyl-taxine B and 5-cinnamoyloxy-taxin B, against oxidative stress injury. Methods : SK-N-SH cells were pretreated with 7-deacetyl-taxine B, 5-cinnamoyloxy-taxin B or DMSO (control) and then incubated with H2 O2 for another 24 h. Cell viability was measured by MTT colorimetric assay. Apoptosis rate, reactive oxygen species (ROS) and mitochondrial membrane potential (MMP) were detected using flow cytometry assay. Ultrastructure was detected by Transmission electron microscope. Results : Taxane-derived compounds improved H2 O2 mediated loss of cell viability in SK-N-SH cell. Ultrastructure of control group cells showed nucleus shrinkage, dense aggregation of chromatin, appearance of apoptotic body and mitochondrial dilation. Treated group showed alleviation of mitochondrial dilation and chromatin margination, and reduction of apoptosis cells induced by H2 O2 . The apoptosis rate was decreased in treated group compared with control group. DCFH-DA staining showed that ROS were significantly decreased in cells treated with taxane-derived compounds compared with control group. Rhodamine123 staining showed that MMP was significantly decreased in cells treated with taxane-derived compounds compared with control group. Conclusion : The anti-oxidative stress and neuroprotective effect of taxane-derived compounds was verified here, wherein it could protect neurocytes from H2 O2 -induced oxidative stress injury.